Biomarkers of severity and chronification in chikungunya fever: a systematic review and meta-analysis - Andreia Silva Ferreira; Nayara Ragi Baldoni; Clareci Silva Cardoso; Claudia Di Lorenzo Oliveira (Revista do Instituto de Medicina Tropical de São Paulo, 2021)
ABSTRACT Currently, there are no biomarkers for Chikungunya fever (CHIK) in clinical practice that can accurately predict the severity or chronification of the disease. The aim of this study is to evaluate the existing literature on biomarkers related to the severity and chronification of CHIK. In this sense, a systematic review was conducted based on the PRISMA Statement guideline. Articles that described the association of biomarkers with the evolution of the disease (severity or chronification), published until August 20th 2019 were considered eligible. The search was carried out in the PubMed, Scopus, Virtual Health Library (VHL) and Science Direct databases. After searching the databases, 17 articles were added to the review, and after analyzing the articles, several biomarkers were associated with severity, such as increased levels of IL-6, IP-10, IL-1b, MIG, MCP-1, and reduced levels of RANTES and IL-8 or chronification, such as increased levels of IL-6, TNF-α, MCP-1, IL-12, INF-α, IL-13, INF-γ, GM-CSF, CRP, IL-1a, IL-15, Factor VII, IP-10, IL-10, IL-4, IL-1RA, IL-8, MIP-1α, MIP-1β, ferritin, MIG, ESR, NO, malondialdehyde, and reduced levels of RANTES, ferritin, eotaxin, HGF, IL-27, IL-17A, IL-29, TGF-β, IL-10, and thiols. IL-6, CRP and TNF-α were included in the meta-analysis to assess the relationship with chronification, although they did not reach statistical significance. It was concluded that several biomarkers showed a relationship with severity and chronification of CHIK; the search for these biomarkers can reveal prognostic factors and important therapeutic targets for the treatment of the disease.